Spojrzenie na modernistyczną tradycję: „Isprani" Zrinka Ogresty i jego polskie źródło literackie - Gilić, Nikica (Przekłady Literatur Słowiańskich, 2023)
Among many contacts and similarities between Croatian and Polish cinematic and literary modernism, it is quite interesting to note that Zrinko Ogresta adapted the writings of Marek Hłasko in his feature film Washed Out (Isprani). The comparison of Ogresta’s film to the literary source, The Eighth Day of the Week (Ósmy dzień tygodnia), before any extensive discussions of wider context, should ascertain the answer to a more elementary question — how close is the story of Ogresta’s film to its Polish literary inspiration?